Embryonal rhabdomyosarcoma of the adult soft palate - Samar Bhutoria; Ciaran ONeil (Wolters Kluwer Medknow Publications, 2011)
Embryonal rhabdomyosarcoma is the most common soft tissue sarcoma in children. We report a rare case of embryonal rhabdomyosarcoma of the soft palate in a 32-year-old Caucasian female. Detailed histology of the tumor is described. Positive staining with desmin, myogenin and myoD1 confirmed the tumor to be embryonal rhabdomyosarcoma. A genetic association between rhabdomyosarcoma, polycystic ovary syndrome and the FEM1A gene on the human chromosome is speculated upon.